2011
DOI: 10.1073/pnas.1015425108
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory network changes in the dentate gyrus restore long-term potentiation following ablation of neurogenesis in young-adult mice

Abstract: It is now well established that neurogenesis in the rodent subgranular zone of the hippocampal dentate gyrus continues throughout adulthood. Neuroblasts born in the dentate subgranular zone migrate into the granule cell layer, where they differentiate into neurons known as dentate granule cells. Suppression of neurogenesis by irradiation or genetic ablation has been shown to disrupt synaptic plasticity in the dentate gyrus and impair some forms of hippocampus-dependent learning and memory. Using a recently dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 38 publications
5
65
1
Order By: Relevance
“…These data indicate that absence of NFATc4 affects the threshold for plasticity induction in the DG when inhibition is intact. They also are in agreement with previous studies showing that a reduction in the number of DG adult-born neurons (35)(36)(37)(38), which have a lower threshold for LTP induction than mature ones (39), results in similar impaired LTP formation.…”
Section: Nfatc4 −/− Mice Show Selective Impairment In the Formation Osupporting
confidence: 82%
“…These data indicate that absence of NFATc4 affects the threshold for plasticity induction in the DG when inhibition is intact. They also are in agreement with previous studies showing that a reduction in the number of DG adult-born neurons (35)(36)(37)(38), which have a lower threshold for LTP induction than mature ones (39), results in similar impaired LTP formation.…”
Section: Nfatc4 −/− Mice Show Selective Impairment In the Formation Osupporting
confidence: 82%
“…Significant alteration of neurogenesis could be one of the contributing factors to diminished plasticity in DS. Interestingly, studies involving mice to different enrichments or pharmacotherapies enhanced both neurogenesis and learning (Deng et al, 2010;Mongiat & Schinder, 2011;Saxe et al, 2006;Shors et al, 2002;Singer at al., 2011), including Ts65Dn mice (Bianchi et al, 2010). Moreover, manipulations that stimulate adult neurogenesis in mice also increase LTP (van Praag et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Another confound to consider when ablating adult neurogenesis was highlighted by Singer et al (2011) who found that although PP LTP was absent 4 wk after ablation (see "Adult hippocampal neurogenesis and its regulation") it returned to control levels by 10-wk post-ablation. To account for this recovery, they showed that GABAergic innervation of matGCs decreases over time following ablation, suggestive of a chronic homeostatic/pathological change to the DG network.…”
Section: Abgcs and Pattern Separationmentioning
confidence: 99%
“…Given that this is typically a chronic manipulation, such studies must consider if the animal may be able to employ alternative strategies to function in the experimental paradigm, if compensatory mechanisms might lessen the impact of ablating adult neurogenesis (e.g., Singer et al 2011), or if there is redundancy in the abGC population when ablation is incomplete. Conversely, false positive results may arise if there are sideeffects associated with the ablation technique (see Box 4).…”
Section: Top-down: Behavioral Effects Of Altering Neurogenesismentioning
confidence: 99%